Transfer of the German Vocational Education and Training System—Success Factors and Hindrances with the Example of Tunisia - Oeben, Melanie; Klumpp, Matthias (Education sciences, 2021)
As the German vocational education and training (VET) system, with its dual learning environment in both firms and vocational schools, is an international benchmark, many concepts and projects are aiming to transfer this approach to other countries and education systems. In such contexts, it is important to consider the specific concepts and requirements of educational transfer. This paper outlines success factors and hindrances for such endeavors. Therefore, a literature review is combined with empirical survey results from Germany. This is directed at a specific project regarding a transfer of the dual VET system from Germany to Tunisia, but it also exemplifies general factors for any such concept transfer. As important success factors, “quality assurance” and “perspectives for graduates”, for example, are identified.